The perspectives of the digital marketing - Porsayev G. (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
The article discusses the challenges the digital transformation is incurring on management. It is important to clarify the role of the leadership in the process of digitalization within company or organization. Therefore, we conducted a brief literature review and discussed the impact of digital transformation.